A Preliminary Study on Comparative Growth and Economic Returns from Rainfed and Irrigated Teak Plantations - Jha, Mohan (Indian Forester, 1999)
A comparative study of three years and three months old rain-fed Teak plantation of Forest Department and intensively managed and irrigated private Teak plantation on adjacent site was carried out. Data collected has been analysed for girth and height growth. Irrigation in early phase of Teak plantation has positive effect on growth of Teak. An attempt has been made to analyse the economics of irrigated and non-irrigated Teak plantation. Analysis reveals that benefit cost ratio in irrigated plantation is 1.48 whereas in non-irrigated plantation it is 1.15. Net profit in irrigated Teak plantation is 2.28 times more than non-irrigated plantation. It is concluded that Teak can be used profitably as farm forestry species.